Makna Bekerja sebagai Guru Honorer di Sekolah Dasar Negeri dalam Pendekatan Fenomenologi - Putrawan, Gde Dharma; Marmoah, Sri; Supianto, Supianto (Universitas Negeri Malang, 2024)
Abstract: The existence of honorary teachers is a reality that exists in the world of Indonesian education. This study examines the meaning of working as an honorary teacher in public elementary schools. The question asked in this study is what it means to work as an honorary teacher in public elementary schools. This research uses qualitative methods with a phenomenological approach. The data collection method in this study was semistructured interviews with open-ended questions. The informants of this study numbered fifteen people consisting of a school superintendent, two principals, and twelve honorary teachers. The results of this study are some people influence the decision of informants to work in public elementary schools. Informants were satisfied despite earning little income while working as honorary teachers. The informants stated that it had individual merit as an honorary teacher. These results can be a reference for researching the lives of honorary teachers.Abstrak: Keberadaan guru honorer merupakan kenyataan yang ada di dunia pendidikan Indonesia. Penelitian ini mengkaji makna bekerja sebagai guru honorer di sekolah dasar negeri. Pertanyaan yang diajukan dalam penelitian ini ialah apa makna bekerja guru honorer di SD negeri. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Metode pengumpulan data dalam penelitian ini yaitu wawancara semiterstruktur dengan pertanyaan terbuka. Informan penelitian ini berjumlah dua belas orang guru honorer. Hasil penelitian ini menunjukkan bahwa terdapat orang-orang yang mempengaruhi keputusan para informan untuk bekerja sebagai guru honorer di SD negeri. Para informan merasa puas walau mendapatkan penghasilan yang sedikit saat bekerja sebagai guru honorer. Para informan menyatakan bahwa memiliki kebermanfaatan individu sebagai guru honorer. Hasil ini dapat menjadi referensi untuk meneliti kehidupan guru honorer.